Os desafios socioeducacionais e comunitários nos processos de reconhecimento e fortalecimento dos Territórios Tradicionais Quilombolas: o caso da Fazenda Candeal - Fonseca, Francisca das Virgens (2021)
This paper aimed to comprehend the contemporary dynamic of traditional quilombola community, through the path of their socio-political and cultural organizations, their social and local contradictions, as well as relationship in the formation of quilombola identity in the rural district of the municipality of Feira de Santana, Bahia. The qualitative approach study, entitled “The socio-educational and communitarian obstacles in the process of recognition and strengthening of the Traditional Quilombola Territories: Fazenda Candeal II’s case” had the goal of analyzing the communitarian processes of political formation in the consolidation of the recognition of quilombola community, Fazenda Candeal II (2010-2018). As analysis categories, were discussed: Traditional Quilombola Community, Education of the Quilombola Field and Contemporary Quilombo. Such authors as José Maurice Arruti (2003; 2008); Abdias Nascimento (2002); Kabenguele Munanga (2006); João José Reis (1989) Clóvis Moura (1986; 1988); Nilma Lino Gomes (2006;2014; Miguel Gonzáles Arroyo (2012;2014); Souza (2010); Souza (2016), along with others, helped support this search. For the empirical research, this study was based on the reports of the members of the Candeal Community Development Association (ACDC), an important local socio-communitarian space, on the process of recognizing the identity and conquest of the quilombola territory. Community reports were made via questionnaires to demarcate the socio-economic profile of the community and semi-structured interviews to reach the narratives of the ancient residents. It is important to emphasize that the local institutional archive also served as community data source, with documents as meeting records, recordings of interviews with older residents at significant moments in local history and photographic archive. Some paths were pointed out in this research, in particular the importance of the history transmitted to the education of the younger generation, the relevance of the awareness of a black and rural identity in the process of appropriation of local quilombola culture and the strength of community organization, factors that led to the guarantee of quilombola social rights, the ownership of the territory and in collective identity of Candeal II. Contrastingly, this study also revealed the absence of a project for quilombola school education based on the precepts of country education that, in fact, corroborates this legacy of history and socio-community recognition at school environment. Understanding the community power, the research subjects demonstrated to recognize the importance of education to consolidate identity processes, however, pointed out the need to strengthen the quilombola identity in the approaches to school education, capable of strengthening community dynamics in the process of training young quilombola students.